Local religiosity and financial advisor misconduct - Cowan, Arnold R.; Gao, Lei; Han, Jianlei; Pan, Zheyao (Journal of Corporate Finance, 2024)
We find that local religious social norms mitigate professional misconduct by financial advisors. Using publicly disclosed misconduct data, we find that financial advisors working in areas with greater religious participation are less likely to violate ethical standards. When advisors move to counties with greater religious participation, their misconduct rates decrease. The effect of local religiosity is robust across population density levels, misconduct types, and market conditions. We strengthen identification by using shocks to religious participation following local disclosures of sexual abuse by Catholic priests. The findings show that local religiosity restrains misconduct not only in previously studied corporate financial settings but also when professionals provide financial services to individuals and households.